The use of forest canopy by various bird species in tropical forest montana zone, the Nature Reserve of Mount Tilu, West Java, Indonesia - RUHYAT PARTASASMITA; ZAMZAM I’LANUL ANWAR ATSAURY; TEGUH HUSODO (Society for Indonesian Biodiversity, 2017)
Abstract. Partasasmita R, Atsuary ZIA, Husodo T. 2017. The use of forest canopy by various bird species in tropical forest montana zone, the Nature Reserve of Mount Tilu, West Java, Indonesia. Biodiversitas 18: 453-457. Availability of vertically or horizontally space on a habitat is needed by birds for their activities. Forest is the habitat that provides vertical space strata more numerous and tend to be inhabited by various species of birds more diverse. Strata of trees canopy provide the resources needed by various species of birds, therefore allowing each canopy strata is utilized by certain bird species. This research aimed to study the use of strata of trees canopy by various species of birds in a tropical forest montana zone, Mount Tilu Nature Reserve, West Java, Indonesia. Opportunistic spot-observation of individual was used to study the activity and the use of space by birds. The results showed that the use of layers of the forest canopy by birds that Emergent: 4 species, Canopy: 29 species, Sub-canopy: 16 species, understorey: 25 species and Ground: 11 species. The use of space position on plants by birds was space on canopy by 8 species, space at the edge of canopy by 33 species, space in canopy by 34 species, space under canopy by 19 species and on the ground by 11 species, with 7 species capable to use 3 space positions on plants. The highest similarity index of canopy layers uses was between canopy and sub canopy layers, with percentage 57.63%. The highest similarity index of position uses was between position of space at the edge of canopy and space in canopy with percentage 53.73%.Keywords: Bird, forest canopy layer, Mount Tilu Nature Reserve, space utilization